IMPLEMENTATION OF ARABIC LANGUAGE LEARNING IN GRADE II OF KUTTAB DARUL ULUM BANJARNEGARA (ANALYSIS OF UNDERSTANDING AND SKILL LEVELS) - Faukon; Zahrodin Fanani (cendekia citra gemilang, 2026)
This study aims to analyze the implementation of Arabic language learning in grade II at Kuttab Darul Ulum Banjarnegara, focusing on students’ comprehension and language skills. This research employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that Arabic learning has been implemented interactively, with active student participation supported by the teacher’s competence in managing the classroom and delivering materials. Students’ comprehension levels are relatively good, particularly in vocabulary mastery and understanding simple instructions. However, language skills development has not been balanced, especially in reading and writing skills, which remain relatively low. In addition, several challenges were identified, including the absence of systematic lesson planning, a lack of initial learning motivation, and limited reflective activities. The study implies the need for strengthening instructional planning, improving motivational strategies, and developing balanced integration of the four language skills. Therefore, Arabic learning is expected to enhance students’ competencies more comprehensively.